Isolated Fourth Nerve Palsy in Nontraumatic Tentorial Hemorrhage. Issue 1 (March 2019) - Walter, Eyal; Trobe, Jonathan D.
Abstract : Abstract: A 46-year-old woman being treated with warfarin for antiphospholipid antibody syndrome experienced a rise in international normalized ratio (INR) to 5.4 and developed sudden headache and diplopia. Neuro-ophthalmologic examination disclosed a right fourth nerve palsy. Noncontrast computed tomography revealed a subdural hematoma layered along the right tentorium cerebelli, directly in the path of the nerve. With normalization of the INR, the palsy markedly improved over subsequent weeks. This is a unique case of a nontraumatic subdural hematoma causing a fourth nerve palsy.